Stillbirth and Live Birth at Periviable Gestational Age: A Comparison of Prevalence and Risk Factors - Carmichael, Suzan L.; Blumenfeld, Yair J.; Mayo, Jonathan A.; Profit, Jochen; Shaw, Gary M.; Hintz, Susan R.; Stevenson, David K. (American Journal of Perinatology, 2019)
Objective We compared the prevalence of and risk factors for stillbirth and live birth at periviable gestational age (20–25 weeks).Study Design This is a cohort study of 2.5 million singleton births in California from 2007 to 2011. We estimated racial–ethnic prevalence ratios and used multivariable logistic regression for risk factor comparisons.Results In this study, 42% of deliveries at 20 to 25 weeks' gestation were stillbirths, and 22% were live births who died within 24 hours. The prevalence of delivery at periviable gestation was 3.4 per 1,000 deliveries among whites, 10.9 for blacks, 3.5 for Asians, and 4.4 for Hispanics. Nonwhite race–ethnicity, lower education, uninsured status, being U.S. born, older age, obesity, smoking, pre-pregnancy hypertension, nulliparity, interpregnancy interval, and prior preterm birth or stillbirth were all associated with increased risk of both stillbirth and live birth at 20 to 25 weeks' gestation, compared with delivery of a live birth at 37 to 41 weeks.Conclusion Inclusion of stillbirths and live births in studies of deliveries at periviable gestations is important.
Keywords: stillbirth; periviable gestation; risk factor; race–ethnicity; preterm delivery